If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5(-1) + -6y = 7 Multiply 5 * -1 -5 + -6y = 7 Solving -5 + -6y = 7 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '5' to each side of the equation. -5 + 5 + -6y = 7 + 5 Combine like terms: -5 + 5 = 0 0 + -6y = 7 + 5 -6y = 7 + 5 Combine like terms: 7 + 5 = 12 -6y = 12 Divide each side by '-6'. y = -2 Simplifying y = -2
| x*x+6x-5=12 | | 2x+15=-3x+5 | | 2+4r=r-6 | | 8(2)+y=16 | | 81m^2-64=0 | | 8x-0.8=9x | | 4x+12=5x-1 | | 3x+1+51=180 | | 4a+3a-9a= | | K^2-625=0 | | 3x+1=51 | | R=pq | | 8n+3=3(2n)-1 | | n+3-5=12 | | y=-1.25(x-5) | | b+5-20=180 | | 2g+5=32 | | 4x*x-11x+14=8x+2 | | 3x-1.5=6 | | 2x+(3x-12)+(4x+9)=360 | | -7x+14=-8x-16 | | y/4-7=8 | | x+5-10=54 | | 8+-2x=7x+82 | | x+x-5+65=180 | | -7x=8-16 | | 3(5x-4)=33 | | 75.00+25.00x=0 | | 6(4f)= | | X^2-33x+245=0 | | 2x+16=3x+24 | | (5+u)(5u-2)=0 |